Analisis Komunikasi Kader Posyandu Dahlia dalam Menyampaikan Informasi Kesehatan Anak di Total Persada Kota Tangerang - Fazrin Salsabilla, Erin; Wati, Lina; Safitri Salsabil, Luna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Integrated Service Post (Posyandu) is part of a government program that is integrated between the community, government, and the private sector. Based on that, cadres have an important role in the success of a Posyandu, therefore researchers are interested in examining the credibility of communicators in this case the Dahlia Posyandu cadres in conveying information about children's health. This study uses a qualitative descriptive analysis method with the theory of source credibility. Data collection techniques with observation, interviews, documentation. The results of the study showed that the Dahlia Posyandu communicators have good skills, this can be seen from the knowledge possessed by the Dahlia Posyandu cadres regarding child health and the clarity of the information conveyed. Furthermore, the results of the study showed that the Dahlia Posyandu communicators are trustworthy, this can be seen from the information conveyed regarding child health to the community. Meanwhile, the Dahlia Posyandu cadres are quite attractive, this can be seen from the Dahlia Posyandu cadres being kind and being able to establish familiarity with the community who come to the Dahlia Posyandu.